295 Effects of Prenatal Testosterone Excess on Puberty Attainment of First-Generation ewe Lambs. (21st September 2022) - Gurule, Sara C; Sustaita, Jessica F; Landers, Renata; King, Leslie; Garza, Viviana; Bynum, Sarah; Arrott, Dylan; Padmanabhan, Vasantha; Cardoso, Rodolfo C
Abstract: Prenatal testosterone excess causes reproductive perturbations in sheep that recapitulate those seen in women with polycystic ovary syndrome (PCOS). Obesity has a significant role in the development and severity of the PCOS phenotype. Our objective was to investigate the effects of testosterone excess from gestational days (GD) 60-90 (unlike the GD 30-90 model, these animals are not virilized) and postnatal body weight (BW) gain on puberty in first-generation ewe lambs. Pregnant Suffolk ewes received testosterone propionate (T; 100 mg) or corn oil (C) i.m. twice weekly from GD 60-90 (term=147d). Ewe lambs were weaned 3 mo of age. Control and T lambs were assigned to gain either 0.3 kg/d (C and T-maintenance) or 0.4 kg/d (T-overfed). Maintenance diet was designed to promote optimal growth without excess fat deposition. Overfed ration was designed to achieve a BW 30% above that of maintenance. Progesterone concentrations were measured via radioimmunoassay in blood samples collected twice weekly from ewe lambs (n=15/group) during the first breeding season. Puberty was defined as when progesterone concentrations were < 0.5 ng/mL for four consecutive samples followed by three consecutive samples ≥0.5 ng/mL. Six animals (C, n=1; T-maintenance, n=3; T-overfed, n=2) did not attain puberty during the study and puberty was assigned as last day of sampling. Average daily gain was not different among treatments (C, 0.23±0.02kg; T-maintenance, 0.25±0.01kg; T-overfed, 0.27±0.02kg). Age at puberty did not differ between groups (C, 274.6±9.9d; T-maintenance, 270.0±11.3d; T-overfed, 266.0±10.2d). Similarly, BW at puberty did not differ across treatments (C, 50.44±2.2kg; T-maintenance, 52.5±2.4kg; T-overfed, 57.3±2.5kg). In conclusion, unlike GD 30-90 exposure which advanced puberty, GD 60-90 exposure did not affect age and BW at puberty in ewe lambs. Collectively, these studies suggest that GD 30-60 is a critical developmental window in which prenatal testosterone excess advances puberty in female sheep. Research support: NIH-NICHD (R01HD099096).